1969
DOI: 10.1017/s0025315400046440
|View full text |Cite
|
Sign up to set email alerts
|

The Component Combined Amino Acids Of Some Marine Diatoms

Abstract: An investigation has been made of the occurrence of 25 amino acids in the hydrolysates of five species of diatoms which had been grown in Erd-Schreiber medium. Their distribution pattern in general resembles that found in other species. However, there are characteristic differences; thus, they contain more serine and 2-amino wo-butyric acid than the other species of phytoplankton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…This value is not valid because it corresponds to that of animal protein. The correct conversion factor for phytoplankton is 5.8 reported by Fraga and Pérez (1990), who obtained the value from a data set of 175 amino acid samples and is close to the value of 5.6 recorded by Chuecas and Riley (1969) for diatoms. On the other hand, to estimate Prt using a factor of 5.8, it is necessary to multiply this value by the 80% of total N in order to remove the N-contribution from chlorophyll and nucleic acids.…”
Section: Discussionsupporting
confidence: 83%
“…This value is not valid because it corresponds to that of animal protein. The correct conversion factor for phytoplankton is 5.8 reported by Fraga and Pérez (1990), who obtained the value from a data set of 175 amino acid samples and is close to the value of 5.6 recorded by Chuecas and Riley (1969) for diatoms. On the other hand, to estimate Prt using a factor of 5.8, it is necessary to multiply this value by the 80% of total N in order to remove the N-contribution from chlorophyll and nucleic acids.…”
Section: Discussionsupporting
confidence: 83%
“…3b than can be predicted from the amount of ammonium assimilation. Based on a protein composition of 14% N by weight in P. tricornutum (Cheucas and Riley 1969), the measured protein value in these cells was 2.4-fold greater than the value predicted from the total amount of ammonium-N assimilated over the period of the experiment. It is possible that these cells are synthesizing a carbon-rich complement of proteins; certainly the protein composition in cells that are not dividing is unlikely to be the same as the composition in those cells that are actively growing.…”
Section: Discussionmentioning
confidence: 72%
“…Release of free amino acids by zooplankton has been found in several investigations (Johannes and Webb 1970, Butler et al 1970, Corner and Davies 1971 but also release during grazing must be taken into consideration Davies 1971, Williams 1975). Therefore the sources of the main amino acids can be phytoplankton material, of which the main amino acids were found to be also glycine, serine and alanine along with aspartic and glutamic acid and leucine (Chuecas andRiley 1969, Hecky et al 1973), as weil as zooplankton, since a similar amino acid dominance was found for Calanus helgolandicus (Cowey and Corner 1963). In short, at this phase decomposition processes were proceeding at the depths where high amino acid concentrations were observed.…”
Section: Discussionmentioning
confidence: 90%
“…11). The increase of up to 40 nmol dm-3 during the phytoplankton maximum was caused by the phytoplankton bloom, since the main compounds of this very labile fraction are typical for diatoms (Chuecas and Riley 1969). These compounds are octadecahexaenoic and eicosapentaenoic acids.…”
Section: Discussionmentioning
confidence: 99%